Implementasi Media Pembelajaran Animasi Dalam Meningkatkan Motivasi Belajar Pendidikan Agama Islam - Eko Nursalim; Gita Astria; Siti Aminah W. Tukan; Haeril Kurniawan Wardhana; Hikmah (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
Learning methods play a crucial role in enhancing the enthusiasm and willingness of students to learn, particularly in the field of Islamic religious education. In this digital era, animation technology has emerged as an excellent approach to improving the quality of education. The objective of this research is to investigate the implementation of technology-based methods used to enhance students' understanding of Islamic religious teachings. Qualitative methods such as observation, interviews, and literature review have been employed in this study. The findings demonstrate that the utilization of animation media can significantly improve students' motivation and eagerness to engage with Islamic sciences. Animation serves as a valuable tool in facilitating a more vivid and interactive comprehension of Islamic religious teachings. Consequently, the integration of technology-based animation in learning can effectively enhance students' educational experience in the realm of Islamic religious education. Further research and practical development initiatives aimed at promoting the essence of Islamic values are expected to yield a positive impact on the field of education. Keywords: Implementation, Technology, Animation, Motivation, Islamic Religious Education.